Research on education in Africa, the Caribbean, and the Middle East, an historic overview - Mutua, Kagendo, 1966-; Sunal, Cynthia S. (Emerald Publishing Limited : Information Age Pub., 2004)
A historical overview of research on education in Africa, the Caribbean and the Middle East. Topics covered include: the challenges and assistance of beginning teaching in Jamaica; learning cognitive skills in Israel; and a feminist analysis of sexual harassment among high school girls in Kenya.
Keywords: Education -- Africa.; Education -- Caribbean Area.; Education -- Middle East.; Education -- History.; History of education.; elektronické knihy; electronic books